Statutory standards for the protection of minors in Church legal conducting charity and care activities - Poniatowski, Miachał (Prawo Kanoniczne, 2023)
The article contains an analysis of statutory standards for the protection of minors in church legal entities conducting charity and care activities. First of all, the article refers to the outline of the protection of minors in canon law. This part contains an indication of many levels of canon law norms regarding the protection of minors. The following section presents an outline of the Act of July 28, 2023. The article also contains a division and presentation of statutory standards, first vertical standards, and then horizontal standards. The results from the analysis are included in the conclusion.